The Empowerment of Family in Effort to Reduce Stunting in Under-Five Children: A Scoping Review - Lulu Annisa; Sulistyaningsih Sulistyaningsih (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Stunting is a chronic nutrition problems causing growth failures in under five years old children. The condition does not only affect physical growth but also brain intelligence which leads to the low quality of human resources and eventually affects national economy. Family empowerment efforts can be one of effective ways to help the government in decreasing stunting case. The study was to review family empowerment in stunting declining efforts in under five years old children. The study applied PRISM-ScR framework in article search through relevant databases namely Pubmed, Proquest and Willey, and then the Critical Appraisal used The Joanna Briggs Institute (JBI). Based on the article search, from 1,493 selected articles, there were 10 articles relevant to the inclusion criteria. In the study, it is revealed that there were 2 main aspects namely socio-demographic and child parenting style. Mothers’ decision making in the household, education, and environment are considered as significant aspects in family empowerment, and they are expected to make changes, improve mothers’ knowledge and skills in child nutritional intake as the effort os stunting decrease. However, further study on social economy, food intake practices, and food variation is important since they are the indicators in fulfilling child nutrition intake which becomes supporting factor in declining stunting cases in under five years old children.  Abstrak: Stunting merupakan masalah gizi kronis yang mengakibatkan gagal tumbuh pada anak di bawah lima tahun. Keadaan ini bukan hanya mempengaruhi pertumbuhan fisik namun mempengaruhi kecerdasan otak sehingga mengakibatkan rendahnya kualitas sumber daya manusia yang berdampak..pada ekonomi negara. Upaya pemberdayaan keluarga dapat menjadi salah satu langkah yang efektif dalam membantu pemerintah menurunkan kasus stunting. Tujuan penulisan studi ini adalah untuk mereview pemberdayaan keluarga dalam upaya penurunan stunting pada balita. Scoping Review ini menggunakan framework PRISMA-ScR dengan pencarian artikel melalui database yang relevan, yaitu Pubmed, Proquest dan Willey kemudian melakukan Critical Appraisal menggunakan The Joanna Briggs Institute (JBI). Berdasarkan hasil pencarian artikel dari 1.493 yang telah diseleksi didapatkan sebanyak 10 artikel yang sesuai dengan kriteria inklusi, dalam tinjauan ini ditemukan dua tema utama yaitu aspek sosio demografi dan pola asuh anak. Pengambilan keputusan ibu dalam rumah tangga, pendidikan dan lingkungan dianggap penting pemberdayaan keluarga yang outcomenya diharapkan dapat membangun perubahan, meningkatkan pengetahuan serta keterampilan ibu dalam pemenuhan kebutuhan gizi anak sebagai upaya penurunan stunting. Namun demikian perlunya dilakukan penelitian lebih lanjut terkait sosial ekonomi, praktik pemberian makan dan keragaman makanan karena hal tersebut merupakan indikator dalam memenuhi kebutuhan nutrisi anak sebagai faktor pendorong dalam menurunkan angka kejadian stunting pada balita.